SPIRITUALITY AND HUMANISM OF MAN OF XXI C. - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article covers the prospects of further existence of man and society by means of the main characteristics of humanity at the beginning of the XXI century.